Mengenal Tipologi dan Kehidupan Pesantren - Muhammad Fahmi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2015)
Knowing the typology and the portrait of life in schools is quiteinteresting, because of the peculiarities of style which is owned boardingschools. Homogeneous character of the Islamic world has gradually meltedand opened by the modern rationalistic civilization. Typology ideal pattern oflife for the people who can be seen in the Islamic world relations systemcentered on clerics have changed. Geographical maps boarding schoolenvironment is a reflection of the kinship system that puts each individual asa citizen in a system that is intact. The important thing is maintained byboarding the prioritization of moral content in the educational process.Whatever innovations developed in schools, the moral remains a majorconcern, so it can not dipugkiri that schools become the most importantmoral fortress in this beloved country.Keywords: typology, life, pesantren